Fine Structure of Rickettsia canada in Tissues of Dermacentor andersoni Stiles - Brinton, Lyle P. (1971)
Preliminary observations on growth and developmental fine structure of Rickettsia canada in various organs and tissues of the hard tick, Dermacentor andersoni Stiles, are reported. R. canada is typically rod-shaped, being delimited with a three-layered wall having a velvety coating adsorbed to its exterior surface. A finely reticulated cytoplasmic matrix containing prominent ribosomes is delimited with a three-layered unit membrane. Average length and width of these organisms are 1.6 by 0.4 μm. Although R. canada produces a generalized infection in D. andersoni, hypodermal and muscle tissues experience heaviest growth. Three morphologically distinct rickettsial forms were observed in individual hypodermal cells: (i) typical growth forms with a finely reticulated cytoplasmic matrix and distinct ribosomes; (ii) atypical forms with lightly to densely staining cytoplasm and a coagulated appearance in which ribosomes cannot be distinguished from the matrix; and (iii) forms with crystalline bodies that have a striated to beaded lattice structure and, at times, a fibrillar body in the cytoplasm as well. Occasional finger-like to irregular invaginations of the plasma membrane are noted. Intranuclear growth was demonstrated by electron microscopy in gut epithelial cells only. Growth and development of R. canada were manifest in all tissues examined.